Factors Related to Work Fatigue in Jambi City Environmental Service Waste Carriers in 2024 - Syahda, Tahira Nabila; Rini, Willia Novita Eka; Hidayati, Fajrina (East Asian Journal of Multidisciplinary Research, 2024)
This research discusses factors related to work fatigue in Jambi City environmental service waste transporters in 2024. The aim of this research is to examine and analyze factors related to work fatigue. This research is a quantitative study with a cross sectional design with univariate and bivariate analysis with a 95% confidence interval. The total population was 165 people and the sample was 108 respondents, the sampling technique used simple random sampling. The research variables are age, length of service, workload, sleep quality, work attitude and heat stress. The results of this study were that 88% of them experienced moderate fatigue and 12% experienced mild fatigue in relation to the variables age (p=0.037), length of service (p=0.003), workload ( 0.006), length of work (p=0.038), work attitude (p=0.029), heat stress (p=0.045) and no relationship with sleep quality (p=0.055) with work fatigue in Jambi City Environmental Agency waste haulers in 2024.